2007
DOI: 10.1002/jbm.a.31763
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic zeolites as a new tool for drug delivery

Abstract: Synthetic zeolites were studied in order to investigate their ability to encapsulate and to release drugs. In particular, a zeolite X and a zeolitic product obtained from a cocrystallization of zeolite X and zeolite A were examined. These materials were characterized by chemical analyses (ICP-AES), X-ray diffraction, nitrogen adsorption isotherm, scanning electron microscopy, laser diffraction, and infrared spectroscopy. Since ketoprofen was chosen as a model drug for the formulation of controlled-release dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 16 publications
0
72
1
Order By: Relevance
“…Another study demonstrated the feasibility of zeolites as a vehicle for drug delivery by releasing ketoprofen under different physiological conditions. 30 We have shown that surface-modified zeolites can release paraquat under controlled conditions. 31 However, this study is the first to demonstrate that zeolite membranes can serve as supports, and we demonstrate this functionality using AgNP for antibacterial use.…”
Section: Resultsmentioning
confidence: 93%
“…Another study demonstrated the feasibility of zeolites as a vehicle for drug delivery by releasing ketoprofen under different physiological conditions. 30 We have shown that surface-modified zeolites can release paraquat under controlled conditions. 31 However, this study is the first to demonstrate that zeolite membranes can serve as supports, and we demonstrate this functionality using AgNP for antibacterial use.…”
Section: Resultsmentioning
confidence: 93%
“…Zeolites crystals are already popular materials as catalysts, adsorbents and ion exchangers, however, they are new materials in the field of drug reservoirs in the delivery of controlled drug [39][40][41] and new categories of biomedical materials. The large pores observed in the zeolite framework made easy the leisurely release of materials so that it can be accepted for medicine delivery implementation [42].…”
Section: Drug-delivering Biomaterialsmentioning
confidence: 99%
“…Zeolite with various types is very potential in this case. X zeolite synthetic has been quite effective with no negative effect when encapsulated on ketopofren drug based on research of Rimoli et al (2007).…”
Section: Introductionmentioning
confidence: 99%